Us and others : social identities across languages, discourses and cultures - Duszak, Anna (Pragmatics & beyond ;, 2002)
It is natural for people to make the distinction between in-group (Us) and out-group members (Others). What is it that brings people together, or keeps them apart? Ethnicity, nationality, professional expertise or life style? And, above all, what is the role of language in communicating solidarity and detachment?The papers in this volume look at the various cognitive, social, and linguistic aspects of how social identities are constructed, foregrounded and redefined in interaction. Concepts and methodologies are taken from studies in language variation and change, multilingualism, conversation.